Analysis of Characteristics of Three Phase Transformer Using MATLAB - Ramadhan, Fakhri; Novalianda, Sari; Sihombing, Panangian Mahadi; Nugraha, Yoga Tri; Irwanto, Muhammad; Md Arshad, Syahrun Nizam; Othman, Mohd Azlishah (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2025)
Three-phase transformers are integral components of modern electrical power systems, serving as the backbone of energy transmission and distribution networks. Their primary purpose is to step up or step-down voltage levels efficiently, enabling the transfer of electrical power over long distances with minimal losses. Due to their widespread use in industrial, commercial, and residential applications, understanding the operational characteristics of three-phase transformers is crucial for improving energy efficiency, ensuring reliability, and optimizing performance. The analysis of transformer characteristics, such as efficiency, voltage regulation, power losses, and behavior under varying load conditions. This research aims to analyze the characteristics of three-phase transformers using MATLAB. The results of the analysis obtained in the study of the characteristics of 3-phase transformers produce an active power (P) of 6183.42 W, a reactive power (Q) of 3832.14 VAR, an apparent power (S) of 7274.61 VA and a transformer efficiency of 97.75% with a time of 0.02 s and produces losses in copper of 81.65 W which forms electromagnetic field radiation where the radiation pattern of the electric field (E field) and the magnetic field (H field) is in the form of a polar graph.